2012
DOI: 10.3109/1354750x.2012.654407
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of risk factors for in-hospital mortality after intensive care unit discharge

Abstract: Charlson comorbidity score, CRP and tracheostomy predicted post-ICU in-hospital mortality.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
15
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 29 publications
2
15
0
Order By: Relevance
“…Many studies that alone were not large enough to show a statistically significant effect (and could have been misinterpreted as there being no effect) contributed to our overall findings [9, 11, 1618, 3741]. One previous meta-analysis of the association between time of discharge from ICU and hospital mortality has been undertaken [46].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Many studies that alone were not large enough to show a statistically significant effect (and could have been misinterpreted as there being no effect) contributed to our overall findings [9, 11, 1618, 3741]. One previous meta-analysis of the association between time of discharge from ICU and hospital mortality has been undertaken [46].…”
Section: Discussionmentioning
confidence: 99%
“…(2012) [16]Paper2008–2009PortugalSingle centreRetrospective cohort,Risk factors for post-ICU in-hospital mortalityMixed medical-surgical (including 7.6% cardiac surgery)None reported20:00–08:00High dependency unit or ward (proportions not stated)16/296(5.4)Azevedo et al (2015) [10]Paper2002–2009CanadaMulticentreRetrospective cohortIn-hospital mortality following out-of-hours ICU dischargeMixed medical-surgicalPatients with missing data ( n  = 399, 1.8%)19:00–07:59Not clearly stated3505/19,622 (17.9)Barker and Flint (2010) [39]Conference abstract2002–2009UKSingle centreRetrospective cohortIn-hospital mortality and readmission following out-of-hours ICU dischargeMixed medical-surgicalPatients with missing data ( n  = 16, 0.3%)16:00–07:59Not stated2565/5145 (49.9)Bramma et al (2012) [37]Conference abstractNot reported (3 year collection period)UKSingle CentreRetrospective cohortIn-hospital mortality following out-of-hours ICU dischargeMixed medical-surgicalPatients with missing data (n not reported)20:00–07:59 a or 17:00–07:59Not stated159/766(20.8)Edie et al (2015) [40]Conference abstract2007–2014UKSingle centreRetrospective cohortIn-hospital mortality following out-of-hours ICU dischargeMixed medical-surgicalPalliative care at discharge ( n  = 80, 2.5%)22:00–06:59Not stated478/3189(15)Gantner...…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…As out-of-hours discharge from an ICU could be considered a marker of premature discharge (the patient is discharged before they are ready because of bed pressures for example) [9] or because discharge out-of-hours may result in a relatively high-intensity patient arriving in area with less staff than in the daytime, resulting in decreased care [10], some authors have looked specifically at the effect of out-of-hours discharge from an ICU as a factor in this high post-ICU mortality rate [1, 2, 11]. There are also many studies which have retrospectively interrogated intensive care databases which may contain information on the effect of out-of-hours discharge [12, 13]. To the best of our knowledge, a systematic review of the association of out-of-hours discharge with in-hospital mortality, incorporating data from both of these two types of studies, has never been undertaken.…”
Section: Introductionmentioning
confidence: 99%
“…The careful assessment of patients' risk at the time of ICU discharge and the promotion of adequate sequential hospital care, namely a more prolonged ICU stay or an intense surveillance in a high-dependency unit [28], may benefit these patients. A potential role for C-reactive protein in identifying this high-risk population has been proposed [29,30].…”
Section: Discussionmentioning
confidence: 99%